Magnetization of ultramafic rocks in the Troodos ophiolite: implications for ridge axis serpentinization and ophiolite emplacement - Qi,L; Muxworthy,AR; Collier,J; Allerton,S (Journal of Geophysical Research: Solid Earth, 2025)
Ultramafic rocks exposed in ophiolites are almost always serpentinized, but it is unclear whether the serpentinization occurs during lithospheric formation or subsequent ophiolite emplacement. The Troodos ophiolite offers an opportunity to discriminate between different serpentinization processes, incorporating rock magnetism, paleomagnetism and forward modeling of field magnetic data. Our results revealed distinct magnetic property zones: weakly magnetic mantle Artemis and Olympus zones, and a highly magnetic lower crust Cumulate zone. The Artemis and Olympus samples have magnetite concentrations <1%, magnetic susceptibility <0.01 SI and natural remanent magnetization (NRM) <4 A/m, consistent with low-temperature serpentinization related to subduction or meteoric water. In contrast, the Cumulate zone rocks have magnetite content up to 8%, magnetic susceptibility up to 0.1 SI and NRM up to 12 A/m, interpreted as high-temperature serpentinite near a spreading ridge. This ridge-related serpentinization is supported by the paleomagnetic results. The Cumulate zone has a mean direction of declination = 280°, inclination = 69°, α95 = 16°, comparable to the direction of the lower crust gabbro, which suggests serpentinization-associated chemical remagnetization during Cretaceous oceanic crust formation. Existing geological, gravity and seismic studies indicate a Pliocene subduction-related serpentinization event which led to the diapir uplift and surface relief of the Artemis and Olympus zones. Ongoing meteoric water-related serpentinization following the exposure of ultramafic rocks has caused surface remagnetization of the Artemis and Olympus zones in the current field.